2018
DOI: 10.1177/1756284818799599
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and its associated factors in microscopic colitis

Abstract: Background:Fatigue is a well-recognized symptom in patients with inflammatory bowel disease and irritable bowel syndrome (IBS), and has been associated with psychological comorbidity and impaired quality of life in both. However, features associated with fatigue in patients with microscopic colitis (MC) are less clear.Materials and methods:We conducted a cross-sectional survey of patients with a new diagnosis of MC including levels of anxiety, depression, somatization, quality of life, and IBS-type symptoms. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
9
0
3
Order By: Relevance
“…The watery diarrhea is often associated with abdominal pain, urgency, incontinence, nocturnal symptoms, and/or weight loss 6,21. Fatigue has also been noted to be a prevalent symptom in MC, as reported by both Nyhlin et al and Kane et al22,23 Fatigue severity was associated with concurrent anxiety, depression, and somatization in MC 23. While a recent systematic review and meta-analysis showed that one in three patients with MC can have symptoms of irritable bowel syndrome, namely alterations in bowel habits and abdominal pain, the rate of symptoms was similar to the general population, despite recent case–control studies showing the opposite 24.…”
Section: General Overviewmentioning
confidence: 93%
“…The watery diarrhea is often associated with abdominal pain, urgency, incontinence, nocturnal symptoms, and/or weight loss 6,21. Fatigue has also been noted to be a prevalent symptom in MC, as reported by both Nyhlin et al and Kane et al22,23 Fatigue severity was associated with concurrent anxiety, depression, and somatization in MC 23. While a recent systematic review and meta-analysis showed that one in three patients with MC can have symptoms of irritable bowel syndrome, namely alterations in bowel habits and abdominal pain, the rate of symptoms was similar to the general population, despite recent case–control studies showing the opposite 24.…”
Section: General Overviewmentioning
confidence: 93%
“…In a cross‐sectional survey of 151 MC patients, 52 (34.4%) reported IBS‐type symptoms and had higher levels of anxiety, depression and somatisation and impaired quality of life 179 . In another cross‐sectional survey of 129 patients with a new diagnosis of MC, fatigue severity resulted to be associated with IBS‐type symptoms, psychological comorbidity and impaired quality of life, with a negative correlation in HRQoL measures 188 . In a cross‐sectional study including 158 female MC patients, those with coexisting IBS‐like symptoms (55%) experienced worse psychological well‐being than those without.…”
Section: Methodsmentioning
confidence: 99%
“…179 In another cross-sectional survey of 129 patients with a new diagnosis of MC, fatigue severity resulted to be associated with IBStype symptoms, psychological comorbidity and impaired quality of life, with a negative correlation in HRQoL measures. 188 In a cross-sectional study including 158 female MC patients, those with coexisting IBSlike symptoms (55%) experienced worse psychological well-being than those without. Also, smoking and PPI were associated with gastrointestinal symptoms and impaired psychological well-being in MC patients.…”
Section: Very Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…2) [2,4,22]. Кроме того, у пациентов с МК могут наблюдаться сильная усталость, тревога и депрессия [4,34]. Важно отметить, что большинство пациентов могут испытывать симптомы заболевания на протяжении 2-3 лет до установления диагноза [35].…”
Section: клиническая картина и критерии диагностикиunclassified